Modeling Of The General Sciences Teaching System In Higher Education Institutions On The Basis Of Interdisciplinary Integration (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article focuses on the effectiveness and results of the work performed on the modeling of the system of teaching general professional subjects based on interdisciplinary integration in higher education institutions.